DSP in the loop implementation of an improved sliding mode control for induction motor drive - El Haissouf, Mohammed; El Haroussi, Mustapha; Ba-Razzouk, Abdellfattah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper deals with the design and processor in the loop implementation of an improved sliding mode control of three-phase induction motor. Studied control strategy uses a state-space model expressed in the rotor flux frame. Proposed control strategy is designed in two steps based in cascaded method. This controller is based on new smooth functions replacing sign functions to reduce chattering phenomenon. This work integrates also a calculation of controller parameters to ensure set response times. It focuses on the study of these proposed techniques and their effect on motor waveforms. For code generation of the control algorithm, implementation and validation by processor in the loop technique we have created a platform based on MATLAB/Simulink with code composer studio as integrated development environment and the development board LAUNCHXL-F28069M from Texas instruments. Obtained results show that the proposed strategy reduces chattering using a simple algorithm.